When does AI pay off? AI-adoption intensity, complementary investments, and R&D strategy. (December 2022) - Lee, Yong Suk; Kim, Taekyun; Choi, Sukwoong; Kim, Wonjoon
Abstract: This paper examines how high-tech venture performance varies with AI-adoption intensity. We find that firm revenue increases only after sufficient investment in AI, and the benefits of AI adoption are greater at firms that also invest in complementary technologies and pursue internal R&D strategy. Specifically, AI adoption at low levels does not suggest significant revenue growth, but, as the intensity of AI adoption increases revenue growth occurs. We find that such performance gains from adoption is larger among firms that invest in complementary technologies such as cloud computing and database systems. Moreover, the positive relationship between AI adoption intensity and revenue growth is stronger among firms that pursue a more exclusive R&D strategy specific to the venture. Highlights: We examine how high-tech venture performance varies with AI-adoption intensity. AI adoption at low levels does not suggest significant revenue growth, but, as the intensity of AI adoption increases revenue growth occurs. We also find that firm revenue increases only after sufficient investment in AI. The relationship between AI adoption intensity and revenue growth increases when firms invest in cloud computing and database systems. The relationship between AI adoption intensity and revenue growth increases when firms pursue exclusive R&D strategies specific to the venture.